Analisa Komparatif Pembiayaan Konsumtif Dan Produktif Koperasi Syariah Muamalah Berkah Sejahterah Surabaya Terhadap Peningkatan Kesejahteraan Anggota - Sari, Layli Intan; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2018)
This study aims to analyze differences of costumer financing and productive financing to members welfare in Muamalah Berkah Sejahterah Surabaya Sharia Cooperative. The research is quantitative with comparative approach. The technique of data analysis is using the analysis of variance. The results showed that there was a significant difference between consumptive and productive financing to increase member welfare